Long-term Results of Domino Liver Transplantation for Hepatocellular Carcinoma Using the "Double Piggy-back" Technique: A 13-Year Experience. Issue 5 (November 2015) - Marques, Hugo Pinto; Ribeiro, Vasco; Almeida, Tânia; Aniceto, João; Silva, Sílvia; Sobral, Mafalda; Mateus, Élia; Martins, Américo; Barroso, Eduardo
Abstract : Objectives: The aim of this study was to evaluate the long-term outcome of liver transplantation (LT) for hepatocellular carcinoma (HCC) with Domino LT (DLT) using the "Double Piggy-back" technique. Background data: DLT using livers from familial amyloidotic polyneuropathy (FAP) patients is a well-described technique and useful for expanding the donor pool. However, data on long-term results for HCC are limited, particularly regarding the use of the "Double Piggy-back" technique. Methods: Between 2001 and 2014, a total of 260 patients undergoing LT for HCC were analyzed from a prospective database. Of those, 114 were submitted to DLT. Comparisons between groups were performed using propensity score matching. Results: Median follow-up was 34 months (1–152). Overall and disease-free 5-year survival rates for the whole population were 58% and 56%, respectively. There were 177 (68%) patients within Milan Criteria and an additional 26 (10%) within University of California San Francisco (UCSF) criteria. Patients older than 50 years were more likely to receive an FAP liver [odds ratio (OR) 1.94, confidence interval (CI) 1.02–3.69]. DLT patients had more major complications (23.7% vs 13.0%, P  = 0.025). Only patients undergoing DLT presented with piggy-back syndrome (7% vs 0%, P  = 0.001). After adjusting for potential confounders, DLT and cadaveric LT had a similar 5-year survival rate (59% vs 44%, respectively, P  = 0.117). Thirteen patients (11.4%) evidenced FAP disease but not before 6 years after DLT. Conclusions: DLT for HCC is feasible and achieves equivalent results to cadaveric LT. The benefit of expanding the donor pool must be balanced against higher morbidity and a real risk of disease transmission. Abstract : Supplemental Digital Content is available in the text